2018
DOI: 10.26858/ijole.v2i2.6360
|View full text |Cite
|
Sign up to set email alerts
|

The USE OF MULTIMODAL TEXT IN ENHANCING ENGINEERING STUDENTS’ READING SKILL

Abstract: Abstract It is believed that the students’ low reading proficiency, as shown in their TOEIC scores, is due to their poor reading habit. One of the ways to overcome such a problem is by facilitating them with a lot of reading practices in an extensive reading program. Since today non-printed multimodal texts (NPMT) and Linear texts (LT) are available in the society, an experiment on which mode is most effective to enhance the students’ reading proficiency needs to be done. This study aims to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…One of the reading processes that occur in reading activities is decoding [25] and driven activities [26]. Meanwhile, reading as a result of communication achievements in the process of transactions or negotiations takes place between readers and writers [27]. These achievements can be in the form of ideas or thoughts which are then called reading comprehension.…”
Section: Reading Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reading processes that occur in reading activities is decoding [25] and driven activities [26]. Meanwhile, reading as a result of communication achievements in the process of transactions or negotiations takes place between readers and writers [27]. These achievements can be in the form of ideas or thoughts which are then called reading comprehension.…”
Section: Reading Skillsmentioning
confidence: 99%
“…Reading is not a passive process but active [27] and [28]. The reader actively tries to capture the contents of the reading.…”
Section: Reading Skillsmentioning
confidence: 99%
“…In addition, some evidence has shown that the use of various modes may bring benefits to students' English learning and teachers' instructional practices. For instance, a study conducted by Cahyaningati and Lestari (2018) reveals the efficacy of multimodal text concerning reading proficiency. Moreover, a multimodal text was found to have the potential to foster students' critical thinking (Al-Qahtani, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The reading difficulties effect low reading comprehension skills. In the meantime, multimodal texts become more popular in education particularly in reading materials (Cahyaningati & Lestari, 2018) and advanced reading skills are essential for success of students (Marschall & Davis, 2012). In this case, A reading skill is a cognitive ability which a person is able to use when interacting with the written texts (Bojovic, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the similar vein, Boshrabadi & Biria (2014) explored the efficacy of multimodal vs. print-based texts for teaching reading comprehension skills to Iranian high school third graders. Moreover, Cahyaningati & Lestari (2018) explored the use of multimodal text in enhancing reading skills.…”
Section: Introductionmentioning
confidence: 99%